Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Determine the value of [tex]\( p \)[/tex] for the series below, using the fact that [tex]\( a^{\log_b(n)} = b^{\log_b(n) \log_b(a)} = n^{\log_b(a)} \)[/tex].

[tex]\[ \sum_{n=1}^{\infty} n^2 \left( 4^{-3 \ln(n)} \right) \][/tex]

Be sure to include parentheses around the arguments of any logarithmic functions in your answer.


Sagot :

To determine the value of [tex]\( p \)[/tex] for the given series, we start with the series:

[tex]\[ \sum_{n=1}^{\infty} n^2 \left( 4^{-3 \ln(n)} \right) \][/tex]

We can use the exponentiation property [tex]\( a^{\log_b(x)} = x^{\log_b(a)} \)[/tex] to simplify the expression inside the sum.

First, let's deal with the term [tex]\( 4^{-3 \ln(n)} \)[/tex]. We can rewrite 4 as [tex]\( 2^2 \)[/tex], so we have:

[tex]\[ 4^{-3 \ln(n)} = (2^2)^{-3 \ln(n)} \][/tex]

This can be simplified further. Using the power rule for exponents:

[tex]\[ (2^2)^{-3 \ln(n)} = 2^{2 \cdot (-3 \ln(n))} = 2^{-6 \ln(n)} \][/tex]

Next, we take advantage of the property of exponents involving logarithms. Recall that [tex]\( 2^{-6 \ln(n)} = n^{\log_2(2^{-6})} \)[/tex]. Therefore:

[tex]\[ 2^{-6 \ln(n)} = n^{-6 \ln(2)} \][/tex]

Since [tex]\( \ln(2) \)[/tex] is a constant, this can be interpreted as:

[tex]\[ 2^{-6 \ln(n)} = n^{-6} \][/tex]

Hence, our original series now looks like:

[tex]\[ \sum_{n=1}^{\infty} n^2 \cdot n^{-6} \][/tex]

We can combine the exponents for [tex]\( n \)[/tex]:

[tex]\[ n^2 \cdot n^{-6} = n^{2 + (-6)} = n^{-4} \][/tex]

So our series is now:

[tex]\[ \sum_{n=1}^{\infty} n^{-4} \][/tex]

This matches the form of a [tex]\( p \)[/tex]-series [tex]\(\sum_{n=1}^{\infty} \frac{1}{n^p}\)[/tex], where [tex]\( p = 4 \)[/tex].

So, the value of [tex]\( p \)[/tex] is:

[tex]\[ p = 4 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.